2020
DOI: 10.6061/clinics/2020/e1801
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-6 level is correlated with the disease activity of systemic lupus erythematosus: a meta-analysis

Abstract: Interleukin-6 (IL-6) plays a crucial role in systemic autoimmunity and pathologic inflammation. Numerous studies have explored serum IL-6 levels in systemic lupus erythematosus (SLE) and their correlation with disease activity. Here, we performed a meta-analysis to quantitatively assess the correlation between the serum IL-6 levels and SLE activity. The PubMed and EMBASE databases were thoroughly searched for relevant studies up to September 2019. Standardized mean differences (SMDs) with 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…Evidence showed an imbalance in Th1/Th2 and other cell subpopulations in patients with SLE, which significantly increased the levels of the pro-inflammatory cytokines IL-6, TNF-α, and IL-1β ( 86 ). IL-6 and IL-1β were known to drive Th17 differentiation and promote the levels of serum IL-21 and IL-17 which correlated with disease activity ( 87 , 88 ). When MSCs exposed to IL-6, the stemness of MSCs was enhanced through an ERK1/2-dependent mechanism ( 89 ); however, whether IL-6 could reduce the immunosuppressive function of MSCs still unclear.…”
Section: Potential Causes Of Msc Therapy Inefficacy In Sle Treatmentmentioning
confidence: 99%
“…Evidence showed an imbalance in Th1/Th2 and other cell subpopulations in patients with SLE, which significantly increased the levels of the pro-inflammatory cytokines IL-6, TNF-α, and IL-1β ( 86 ). IL-6 and IL-1β were known to drive Th17 differentiation and promote the levels of serum IL-21 and IL-17 which correlated with disease activity ( 87 , 88 ). When MSCs exposed to IL-6, the stemness of MSCs was enhanced through an ERK1/2-dependent mechanism ( 89 ); however, whether IL-6 could reduce the immunosuppressive function of MSCs still unclear.…”
Section: Potential Causes Of Msc Therapy Inefficacy In Sle Treatmentmentioning
confidence: 99%
“…Due to the lack of a pericytes cell line, we utilized 10T1/2 cells of mesenchymal stem cell origin, which are widely used for studying pericyte biology in various organs including kidney (4749). As an increase in IL-6 has been reported in the pathogenesis of kidney disease, (5052) we explored its function in STAT3 mediated proliferation, migration, and induction of fibrotic signaling in 10T1/2 cells. We found that pSTAT3 is increased and translocated to the nucleus after IL-6 treatment, and this was inhibited by stattic, a specific inhibitor of STAT3, indicating that these cells responded to IL-6 ( Figure 4A, B, C and D ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was shown that also in patients with SLE the IL-6 expression correlates with disease activity [ 34 ]. Comparatively, therapy with tocilizumab, an anti-human IL-6 receptor antibody, did not show the hoped-for therapeutic success in the case of SLE [ 35 ].…”
Section: Discussionmentioning
confidence: 99%